Estudio de factibilidad para la creación de una empresa dedicada a la extracción y comercialización de aceite de aguacate en el Distrito Metropolitano de Quito - Toapanta Valenzuela, Denisse Marcela (2022)
The present research focuses on a feasibility study for the creation of a company dedicated to the extraction and marketing of Avocado Oil in the Metropolitan District of Quito, to reduce the health problems of this population and the lack of companies dedicated to this type of production, this research has been designed under these needs, technical conditions and service to be offered; the main objective is the preparation of a technical and economic study to determine the feasibility of setting up a company dedicated to the extraction and marketing of avocado oil, so a market study was carried out to define the unsatisfied demand and the marketing system, for this purpose a productive system was defined for the operation and creation of the plant, finally an economic analysis to establish the operating costs and determine the viability and profitability of the project; this research is descriptive, the type of method applied is inductive, the research techniques are field observation, bibliographic research and survey; with the results obtained the feasibility of the project is demonstrated, we can highlight that an initial investment of 129,882.96$ will be needed, the NPV is $2,219,833.98, and the IRR is 43% in relation to the TMAR of 20%; therefore the project is feasible.